Money Politics: External Sanctions and Legal Vacuums in Pemilukada - Reza Ananda (Fox Justi : Jurnal Ilmu Hukum, 2025)
The practice of money politics in general elections, especially regional head elections (Pilkada), is a serious violation of democratic principles. It involves giving or promising money to influence voter behavior, which can damage the integrity of the electoral process. Although there are regulations that regulate the prohibition of money politics, as stated in Law Number 10 of 2016 and Law Number 7 of 2017, law enforcement against these violations is often weak and ineffective. Sanctions for money politicians include prison sentences ranging from 36 to 72 months and significant fines, but the implementation of these sanctions is rarely seen in practice. This study aims to analyze the practice of money politics in the Regional Head Election (Pilkada) in Indonesia, identify the factors that cause it, as well as its impact on the quality of democracy. The research method used is qualitative with a literature study approach. The results of the study show that money politics is still a crucial problem caused by the low level of public education, economic factors, weak supervision and law enforcement, patron-client culture, and the role of political parties that are not optimal. This practice negatively impacts the integrity of the electoral process, produces unqualified leaders, and reduces public trust in the political system. To address this problem, comprehensive efforts are needed through increased political education, strict law enforcement, political party reform, strengthening participatory oversight, and reforming the campaign funding system. It is hoped that this effort can minimize the practice of money politics and improve the quality of democracy in Indonesia.